THE INFORMATION LITERACY AND VERBAL CREATIVITY OF TRAINEE TEACHERS OF TECHNOLOGIES - Valantinaitė, Ilona (European Scientific Journal, ESJ, 2014)
The paper explores the information literacy and verbal creativity of female trainee teachers of Technologies (3rd year students) in Lithuania. Their information literacy was determined applying Mažeikienė et al.’s (2008) test for identifying information literacy, and verbal creativity was analyzed by means of Torrance’s technique of personal creativity diagnostics (a verbal expression questionnaire). The paper analyzes the relation between the informants’ information literacy and verbal creativity.